Improving outcome in severe trauma: what's new in ABC? Imaging, bleeding and brain injury. Issue 1044 (21st July 2012) - Harris, Tim; Davenport, Ross; Hurst, Tom; Hunt, Paul; Fotheringham, Tim; Jones, Jonathan
Abstract : Appropriate imaging is critical in the initial assessment of patients with severe trauma. Plain radiographs remain integral to the primary survey. Focused ultrasonography is useful for identifying intraperitoneal fluid likely to represent haemorrhage in patients who are shocked and also has a role in identifying intrathoracic pathology. Modern scanners permit a greater role for CT, being more rapid and exposing the patient to less ionising radiation. 'Whole body' (head to pelvis) CT scanning has been shown to identify injuries missed by 'traditional' focused assessment and may be associated with an improved outcome. CT identifies more spinal injuries than plain radiographs, is the gold standard for diagnosing blunt aortic injury and facilitates non-operative management of solid organ injury and other bleeding. Coagulopathy occurs early in trauma as a direct result of injury and hypoperfusion. Damage control resuscitation with blood components is associated with an improved outcome in patients with trauma with massive haemorrhage. Packed cells and fresh frozen plasma should be used in a 1:1 to 1:2 ratio. Bedside measures of coagulopathy may prove useful. Adjuvant early treatment with tranexamic acid is of benefit in reducing blood loss and reducing mortality. Limited 'damage control surgery' with early optimisation of physiology augmented by interventional radiology to control haemorrhage is preferable to early definitive care. Limiting haemorrhage by correction of anticoagulation and minimising secondary brain injury through optimal supportive care is critical to improving outcome in neurotrauma.